ASUHAN KEBIDANAN IBU BERSALIN DENGAN PERDARAHAN POST PARTUM PADA NY. “N” DI BPM BIDAN LILIS NURHASANAH, S.ST.KEB, SKM TAHUN 2019 - Ika Apriyanti; Rizka Youliawaty (Poltekkes 'Aisyiyah Banten, 2019)
Post partum hemorrhage is bleeding that exceeds 500 ml after the baby is born. In general, if there is bleeding that is more than normal, especially if it has caused changes in vital signs (such as decreased consciousness, pale, unsteady, cold sweats, shortness of breath, and tension <90 mmHg and pulse> 100 / minute), then treatment must be done immediately. According to USAID Jalin Banten in 2016 there were 240 cases of maternal deaths in Banten and 38% of them were caused by bleeding. This study was conducted so that students were able to provide midwifery care for postpartum hemorrhage cases in Ny.